The Akal Academies - Ghura, Amarpreet Singh; Chand, P. G. Vijaya Sherry (London : Indian Institute of Management, Ahmedabad, 2017)
In July 2016, Baba Iqbal Singh Kingra Ji (Babaji), Chairperson, The Kalgidhar Trust/Society (TKTS), a non-profit social development organisation based at Baru Sahib in Himachal Pradesh, a state in northern India, wanted a plan for expanding the rural school activities of TKTS. As of July 2016, TKTS ran 129 schools that catered to 62,000 students. Starting with one school in 1986, the TKTS chain had grown to 101 schools by 2012, at which point in time TKTS fixed a target of 500 academies with 250,000 students to be achieved by 2020 and adopted a loan-driven model for financing the capital costs of new schools. Previously, TKTS had relied on a donations-based low-cost financial model. Though TKTS provided the capital investments, it expected its schools to become self-sufficient as soon as possible; it believed that with an enrolment of 500 children, a school could take care of its operational expenses with fee income alone. TKTS could continue with its current model of taking loans to finance expansion, or it could consider four other options. The first was the franchising model. The second was for TKTS to enter into management contracts with existing schools, without actually taking over the ownership of the schools. The third option was to increase the leasing of land from Sikh religious bodies and lease land from farmers to cut down on the capital costs. Finally, TKTS could enter into a public-private partnership with the government, under which government schools could be run by TKTS.
Originally published in Ghura, A., & Chand, V. (2017). The Akal Academies. RJMC0043. Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Singh, Iqbal, -- active 2016.; The Kalgidhar Trust/Society.; Nonprofit organizations -- Finance